APPLICATION TECHNOLOGY IN THE USE OF SOIL CORRECTIVES - Saburo Shimada, Belmiro; do Socorro Cunha, Letícia; Vinícius Simon, Marcos (Revista Brasileira de Engenharia de Biossistemas, 2021)
The objective of the work was to carry out a brief literature review on application technology in the use of soil correctives. Based on bibliographic research on the topic of application technology in the use of soil correctives. Application technology is the use of technologies and procedures, in a technical, efficient, safe and careful way for the proper application of products. As most soils are limited by acidic conditions, liming is used to improve the chemical conditions of the soil for plant cultivation. Thus, the application technology in the use of correctives in the soil, allows better application of these correctives in the soil. The correction of acidity must be carried out for the development of plants and the application technology makes it possible to improve the quality of application of these correctives in the soil.